Dunstaple - Bent, Margaret (London Oxford university press, 1981)
John Dunstaple (or Dunstable) (c. 1390 - 24 December 1453) was an English composer of polyphonic music of the late medieval era and early Renaissance. He was one of the most famous composers active in the early 15th century, a near-contemporary of Leonel Power, and was widely influential, not only in England but on the continent, especially in the developing style of the Burgundian School.